Information Anxiety and Use of Social Media for Academic Activities by Undergraduates of University of Ibadan, Nigeria (2020)
Previous studies on Information Anxiety (IA) and Use of Social Media (UoSM) for academic activities have examined factors that influence each of these variables, but there is dearth of literature on influence of IA on UoSM among students, especially in Nigeria. This study, therefore, was designed to determine IA as predictor of UoSM for academic activities, among undergraduates of University of Ibadan, Nigeria. The survey design of correlational type was adopted, while a two-stage sampling procedure was used to select a sample of 165 students. The instruments used were IA (α=0.77) and UoSM (α=0.72) scales. Data were analyzed using descriptive statistics, Pearson’s product moment correlation and Multiple regression at 0.05 level of significance. The most common academic activities for which the undergraduates use social media, were ‘private learning’ ( =3.40) and ‘information exchange with colleagues’ ( =3.34), against the threshold mean value ( =2.50). WhatsApp was the most frequently used social media ( =5.17), while the greatest challenge was ‘use of social media for academic activities is ambiguous’ (=2.52), compared to threshold mean values, =3.50 and =2.50 respectively. The level of information anxiety was low, and IA (r=0.15) did not have significant relationship with UoSM. Information anxiety was positively correlated to use of social media for academic activities by undergraduates of University of Ibadan, Nigeria. Therefore, this factor and the challenges encountered by students in using the social media for academic activities, should be considered by university managements in the country.